Multiple Beneficial Lipids Including Lecithin Detected in the Edible Invasive Mollusk Crepidula fornicata from the French Northeastern Atlantic Coast - Flore Dagorn; Florence Buzin; Aurélie Couzinet-Mossion; Priscilla Decottignies; Michèle Viau; Vony Rabesaotra; Gilles Barnathan; Gaëtane Wielgosz-Collin (Marine Drugs, 2014)
The invasive mollusk Crepidula fornicata, occurring in large amounts in bays along the French Northeastern Atlantic coasts, may have huge environmental effects in highly productive ecosystems where shellfish are exploited. The present study aims at determining the potential economic value of this marine species in terms of exploitable substances with high added value. Lipid content and phospholipid (PL) composition of this mollusk collected on the Bourgneuf Bay were studied through four seasons. Winter specimens contained the highest lipid levels (5.3% dry weight), including 69% of PLs. Phosphatidylcholine (PC) was the major PL class all year, accounting for 63.9% to 88.9% of total PLs. Consequently, the winter specimens were then investigated for PL fatty acids (FAs), and free sterols. Dimethylacetals (DMAs) were present (10.7% of PL FA + DMA mixture) revealing the occurrence of plasmalogens. More than forty FAs were identified, including 20:5n-3 (9.4%) and 22:6n-3 (7.3%) acids. Fourteen free sterols were present, including cholesterol at 31.3% of the sterol mixture and about 40% of phytosterols. These data on lipids of C. fornicata demonstrate their positive attributes for human nutrition and health. The PL mixture, rich in PC and polyunsaturated FAs, offers an interesting alternative source of high value-added marine lecithin.